2004
DOI: 10.1103/physreva.69.032712
|View full text |Cite
|
Sign up to set email alerts
|

Second-order Born model for two-electron atomic ionization by fast charged-particle impact

Abstract: We develop a theoretical model to describe simultaneous ionization excitation and double ionization of a two-electron atomic shell (i.e., He 1s 2 ) by a fast charged-particle impact. The model accounts for the projectile-target interaction to the second order whereas the interaction of the two target electrons ejected into continuum is treated nonperturbatively by the convergent close-coupling (CCC) method. In the second-order term, all intermediate states of the target between two subsequent interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 28 publications
7
34
0
Order By: Relevance
“…1 and 2, we show calculations with three groundstate wave functions: Pluvinage, Le Sech, and Hylleraas. In addition, the calculations were performed utilizing the first and second Born approximations [14] and found to be different by less then 10% (although not quantified, a similar conclusion was reached in Ref. [20]).…”
Section: ͒ ͑3͒mentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2, we show calculations with three groundstate wave functions: Pluvinage, Le Sech, and Hylleraas. In addition, the calculations were performed utilizing the first and second Born approximations [14] and found to be different by less then 10% (although not quantified, a similar conclusion was reached in Ref. [20]).…”
Section: ͒ ͑3͒mentioning
confidence: 99%
“…Following the implementation of the second Born term [14] we are able to test the contribution of this term for the kinematics considered here. We have also implemented the Pluvinage ground state and its improved version as prescribed by Le Sech and co-workers [15,16], who argued that the former lacked the screening of two-particle interactions by the third particle.…”
mentioning
confidence: 99%
“…Kheifets [11] has shown that the second Born approximation, which well describes the TS2 mechanism, is important at 0.5 keV and weak for higher incident energies, as shown by Rasch et al [12] and by El Mkhanter and Dal Cappello [13]. So we consider here only the SO and TS1 mechanisms and perform calculations for future (e, 3e) and (e, 3 − 1e) experiments by giving the best choices for the kinematical conditions.…”
mentioning
confidence: 99%
“…The TS2 mechanism is then a second order process that can only be described within the 2nd Born approximation. However, up to now, only few models have been reported within the secondorder Born approximation, the major part of them being limited to simple atomic targets [39][40][41][42][43][44][45][46]. Considering the double ionization of molecular targets, to the best of our knowledge there are only two available models in the literature that use the 2nd Born approximation for describing the double ionization of H 2 [47,48].…”
Section: Experimental/theoretical Study Referencesmentioning
confidence: 98%